Evolution of stability enhancement in organo-metallic halide perovskite photovoltaics-a review. (June 2021) - Jeevaraj, M.; Sudhahar, S.; Kumar, M. Krishna
Graphical abstract: Highlights: Instability of the MAPbI3 due to ion migration and the extrinsic factors analysed. By reducing ion migration to improve the performance, stability of perovskites analysed. Solvent engineering approach to improve the stability of organo metal halide perovskites reviewed. Surface passivation on the perovskites and extrinsic influencing factors on stability were analysed. Mixed halide engineering approach was detailed. Abstract: The excellent photo-physical properties of organo halide perovskites along with the higher carrier mobility and longer diffusion lengths has led to a maximum power conversion efficiency (PCE) of 25.2 % in a much short span. However, the intrinsic instability due to ion migration and the extrinsic factors such as moisture, UV light, oxygen, and thermal stress limits the durability of these perovskite solar cells (PSC). Understanding the degradation mechanisms and the subsequent stability enhancement strategies provide a useful insight in the fabrication of enduring perovskite solar cells. In this article, the recent progress in improving the stability using different methodologies such as compositional engineering, defect passivation, additional interlayers with hydrophobic properties, other additives that helps in energy level matching of the perovskite layer with the transport layers are summarized. In addition to temperature, other extrinsic factors such as UV light, moisture and oxygen also influence the stability of the perovskites degradation are reviewed.